Prevalence of anemia in patients with chronic kidney disease in conservative treatment (Research, Society and Development, 2022)
It is estimated that more than ten million individuals have chronic kidney disease in Brazil, according to data from the Brazilian Society of Nephrology. Chronic kidney disease is characterized by the progressive and irreversible loss of kidney function, leading to a large number of complications, with anemia being one of the most important and prevalent during its evolution. Objectives: To evaluate the prevalence of anemia in patients with chronic kidney disease undergoing conservative treatment, in a clinic in the west of Paraná. Methodology: Retrospective longitudinal study, using the analysis of medical records of 126 patients from the Nephrology Outpatient Clinic of the Centro Universitário da Fundação Assis Gurgacz - Cascavel (Paraná), treated from 2015 to 2021. Results: The prevalence of anemia in the disease chronic kidney disease was 36.2%, being more common in stages 3 and 4. Conclusion: The prevalence of anemia in the study population was high.